PERANCANGAN SISTEM INFORMASI PENGARSIPAN BUKTI TRANSAKSI PEMBAYARAN BERBASIS WEB DI PT NUSANTARA TURBIN DAN PROPULSI - Muharram, Agung; Muthmainnah; Sufyana, Candra Mecca (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
PT Nusantara Turbine and Propulsion is a company engaged in the maintenance, repair and overhaul (MRO) of gas turbines on an airplane engine. The research conducted to design Payment Transaction Proof Filing Information System at PT Nusantara Turbine and Propulsion with the aim of producing a web-based application that plays a role in digitally collecting documents that were previously done manually. The research method for developing these applications uses SDLC (Problem identification, Data analysis, Design, Testing, Implementation, and Maintenance) & UML. This web application uses MYSQL & APACHE as a local server and is created using PHPRAD. UML plays a role in representing the workflow of a system. The result of this research is a web-based proof of payment transaction archiving application that aims to make it easier for workers when archiving, such as searching and storing documents so that it can be done digitally.